Analisa Kerusakan Bearing Arm Pada Mesin Can Seamer - Junaidi; B Pradana; F A Kurniawan (Cered Indonesia Institute, 2023)
Can seamer is a food and beverage can cover machine with a body made of stainless steel. This machine has a simple and simple way of working, ie the operator fills the can with the product then places the tin lid right on the lips of the can and then places it in the machine and then the Can Seamer will make a depressant. If sales are high, the work of can seamer is also very high. Maintenance or maintenance of machinery and equipment carried out is very necessary in carrying out production process activities so that it can run smoothly. Maintenance or maintenance of machinery and equipment is one of the very important functions in ensuring the smooth implementation of production process activities. The research method used in the study was the study of literature and the application of preventive and corrective maintenance methods. The type of damage that often occurs in the Can Seamer machine is the pressure ridge component that often cannot pressure this because the engine is not carried out in accordance with the use of the procedure. The results of the study in this study were to use the type of maintenance preventice maintenance where the company would incur costs for corrective maintenance of Rp. 45,900,000 per year. When compared, the company will make a preventive of Rp. 24,000,000 per year, then the difference in maintenance is Rp.21,900,000.